2008
DOI: 10.1080/14786410701875686
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of extracts and flavonoid compounds fromOxytropis falcateBunge

Abstract: The antioxidant properties of the various extracts and flavonoids prepared from Oxytropis falcate Bunge were investigated by 1,1-diphenyl-2-picryldydrazyl (DPPH) radical-scavenging assay. In the chloroform, ethyl acetate and n-butanol extracts, the ethyl acetate extract exhibited the highest antioxidant activity (IC(50) = 2.05 mg mL(-1)). Furthermore, rhamnocitrin, kaempferol, rhamnetin, 2',4'-dihydroxychalcone and 2',4', beta-trihydroxy-dihydrochalcone were purified from chloroform and ethyl acetate extracts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Sakuranetin is the major flavonoid found in rice [45] and it has been primarily studied for its anti-inflammatory [46], anti-diabetic [47], and anti-bacterial [48] properties. Rhamnetin is found in most buckthorns (rhamnus genus) [49] and has been primarily studied for its anti-cancer [50], antioxidant [51] and anti-inflammatory properties [41]. Thus, both rhamnetin and sakuranetin have been found to be anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Sakuranetin is the major flavonoid found in rice [45] and it has been primarily studied for its anti-inflammatory [46], anti-diabetic [47], and anti-bacterial [48] properties. Rhamnetin is found in most buckthorns (rhamnus genus) [49] and has been primarily studied for its anti-cancer [50], antioxidant [51] and anti-inflammatory properties [41]. Thus, both rhamnetin and sakuranetin have been found to be anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have showed the importance of their antiradical activity [10-13]. Moreover, their actions in humans have been subject of extensive research, and natural flavonoids have been described to possess several biological activities such as antioxidant, anti-inflammatory, antitumor, and antiviral properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were identified as quercetin (Zheng et al 2009), rutin (Marta et al 2016), verbascoside (Cao et al 2016), genistin (Yin et al 2013), kaempferol (Jiang et al 2008), isorhamnetin (Zheng et al 2009) and naringin (Xu et al 2015), respectively, by comparing the spectroscopic data with those of published values (Supplementary material).…”
Section: Structure Elucidation and Identificationmentioning
confidence: 99%